Insecurity and Assessment Practices in University - Kelechi J.P. Ihechu; Adekunle T. Olutola; Rafiu A. Olatoy (Indonesian Journal of Multidiciplinary Research, 2023)
The study examined the relationship between insecurity and assessment practices in universities in Katsina State, Nigeria. The study adopted a correlation research design. The population was made up of 14,963 final-year students in the two public universities in Katsina State. A sample of 372 students from two universities was used for this study. This sample size was determined by cluster random sampling techniques. The instruments for data collection were sets of constructed rating scales titled Insecurity Rating Scale (IRS), Lecturers Instructional Assessment Procedure Scale (LIAPS), and Students’ Test-taking Practice Scale (STTPS). The rating scales were validated by three specialists in Educational Measurement and Evaluation for face and content validity before administering them to the respondents. The reliability of the instruments was established at 0.76, 0.78, and 0.77 for IRS, LIAPS, and STTPS respectively using the Cronbach alpha statistic. The research questions were answered with PPMCC while the hypotheses were tested with simple linear regression at a 0.05 level of significance. It was found among others that there is a very low correlation between insecurity and assessment practices in universities in Katsina State. This indicates that as insecurity increases, assessment practices decrease in universities, showing a converse link between the variables. It was recommended that since insecurity negatively affects assessment in universities, the state and federal government should ensure that security officers are provided in the universities to improve Lecturers' instructional assessment.